Evaluation and quantification of geographical differences in wound complication rates following the extended lateral approach in displaced intra-articular calcaneal fractures – A systematic review of the literature. Issue 10 (October 2017) - Backes, M.; Spierings, K.E.; Dingemans, S.A.; Goslings, J.C.; Buckley, R.E.; Schepers, T.
Abstract: Introduction: Calcaneal fracture surgery is often performed via the extended lateral approach (ELA). Large differences are reported in literature on wound complication rates. Aim was to perform a systematic review on reported postoperative wound complication (POWC) and postoperative wound infection (POWI) rates following the ELA and evaluate and quantify geographical differences. Methods: A literature search was conducted in the MEDLINE and EMBASE databases and Cochrane Library. Studies before 2000, with <10 patients, biomechanical studies and reviews were excluded. No restrictions regarding language were applied. Results: 3068 articles were identified of which 123 were included, with 8584 calcaneal fractures in 28 different countries. The average total number of POWC was 14.3%, with 3.8% of superficial and 2.2% of deep infections. The highest POWI rate was found in Europe (12.1%) and the lowest in North America (2.8%). A significant difference in incidence of deep POWI between continents was detected (median 0–3.8%). No differences were found in incidence of POWC and POWI between retro- and prospective studies (respectively p = 0.970, p = 0.748) or studies with <10 or ≥10 operations per year (respectively p = 0.326, p = 0.378). However, lower rates of POWI were found in studies with a follow up of >3 months (p = 0.01). Conclusion: Large differences were detected in incidence of POWC and POWI following calcaneal fracture surgery with the ELA between countries and continents. We did not find a lower POWC or POWI rate in retrospective studies compared to prospective studies, larger studies or in studies in which more patients were treated annually. However, the rate of POWI was significantly lower in studies with a follow up of >3 months. We advise the use of a reliable postoperative complication registration system and uniformity in the use of standardized definitions of wound complications for calcaneal fracture surgery.